Contemporary internet communication against traditional communication - Lewandowska-Tomaszczyk, Barbara (Język(i) w czasie i przestrzeni, 2021)
The paper presents dynamics of communicative discourse across time and the profiles of contemporary Computer-Mediated Communication users against traditional communication contexts. The first part focuses on a comparison of the two types of communication and the processes of their hybridisation taking place in the Internet space. In the second part interactional computer communication models are presented in terms of emerging CMC varieties.